Creating Contacts Between Replication and Movement at Plasmodesmata – A Role for Membrane Contact Sites in Plant Virus Infections? - Levy, Amit; Tilsner, Jens (Frontiers in Plant Science, 2020)
To infect their hosts and cause disease, plant viruses must replicate within cells and move throughout the plant both locally and systemically. RNA virus replication occurs on the surface of cellular membranes that become extensively modified in the process. Viruses co-opt components of membrane contact sites (MCS) to harness the non-vesicular lipid-shuttling capacity of these structures and thus create a suitable membrane environment for their replication. Whereas animal viruses exit and enter cells when moving throughout their host, the rigid wall of plant cells obstructs this pathway and plant viruses therefore move between cells symplastically through plasmodesmata (PD). PD are membranous channels connecting nearly all plant cells and are now viewed to constitute a specialized type of endoplasmic reticulum (ER)-plasma membrane (PM) MCS themselves. Thus, both replication and movement of plant viruses rely on MCS. However, recent work also suggests that the replication and movement of plant viruses are closely coupled at ER-PM MCS at the entrances of PD. Movement-coupled replication at PD may be distinct from the main bulk of replication and virus accumulation, which produces progeny virions for plant-to-plant transmission. Thus, MCS play a central role in plant virus infections, and may provide a link between two essential steps in the viral life cycle, replication and movement. Here, we provide an overview of plant virus-MCS interactions identified to date, and place these in the context of the connection between viral replication and cell-to-cell movement.